Topical Dopamine Application on Form-Deprivation Myopia in Rabbits - Dong Hyun Kim; Jeong-Min Hwang; Hee Kyung Yang (Life)
Background/Objectives: This study aimed to investigate the efficacy of topical dopamine administration in inhibiting form deprivation (FD) myopia in a rabbit model. Methods: A total of 16 neonatal New Zealand white rabbits were randomly assigned to two groups: a control group and a dopamine treatment group. FD myopia was induced in both groups by applying a light diffuser to one eye. The dopamine group received daily topical instillations of 4% dopamine in the eye with FD myopia, while the control group received normal saline instillations over a four-week period. Axial length measurements were taken to assess the degree of myopia, and histological analysis was performed to evaluate retinal safety and structural integrity. Results: The results indicated that dopamine treatment significantly inhibited axial elongation of the FD eyes compared to the control group, with measurements of 15.07 ± 0.34 mm for the dopamine group versus 15.63 ± 0.33 mm for the control group (p = 0.015). Histological analysis showed no evidence of structural alterations or apoptosis in the retina, confirming the safety of topical dopamine. Conclusions: Topical dopamine appears to be a promising therapeutic approach for controlling the progression of myopia in a rabbit model, demonstrating significant efficacy in reducing axial elongation without inducing ocular toxicity. These findings highlight the potential of dopamine in managing myopia and warrant further investigation in clinical settings.